HDAC6 Mediates Poly (I:C)-Induced TBK1 and Akt Phosphorylation in Macrophages - Wang, Yan; Wang, Ke; Fu, Jian (Frontiers in Immunology, 2020)
Macrophages are derived from monocytes in the bone marrow and play an important role in anti-viral innate immune responses. Macrophages produce cytokines such as interferons and IL-10 upon viral infection to modulate anti-viral immune responses. Type I interferons (IFNs) promote anti-viral defense. IL-10 is a suppressor cytokine that down-regulates anti-viral immune responses. HDAC6 is a tubulin deacetylase that can modulate microtubule dynamics and microtubule-mediated cell signaling pathways. In the present study, we investigated the potential role of HDAC6 in macrophage anti-viral responses by examining poly (I:C)-induced IFN-β and IL-10 production in mouse bone marrow-derived macrophages (BMDMs). We also investigated the role of HDAC6 in poly (I:C)-induced anti-viral signaling such as TBK1, GSK-3β, and Akt activation in mouse BMDMs. Our data showed that HDAC6 deletion enhanced poly (I:C)-induced INF-β expression in macrophages by up-regulating TBK1 activity and eliminating the inhibitory regulation of GSK-3β. Furthermore, HDAC6 deletion inhibited poly (I:C)-induced suppressor cytokine IL-10 production in the BMDMs, which was associated with the inhibition of Akt activation. Our results suggest that HDAC6 modulates IFN-β and IL-10 production in macrophages through its regulation of TBK1, GSK-3β, and Akt signaling. HDAC6 could act as a suppressor of anti-viral innate immune responses in macrophages.